Intraalveolar TNF-α in Combined Burn and Inhalation Injury Compared With Intraalveolar Interleukin-6. Issue 2 (March 2015) - Stromps, Jan-Philipp; Fuchs, Paul; Demir, Erhan; Grieb, Gerrit; Reuber, Kai; Pallua, Norbert
Abstract : The objective of this study was to evaluate the role of intraalveolar tumor necrosis factor-α (TNF- α ) and interleukin-6 (IL-6) in a combination of skin burn and smoke inhalation injuries because this combined trauma is associated with an increased morbidity and mortality compared with either of these traumas alone. We used a standardized small animal model (rats n = 84) to investigate the early intraalveolar excretion of TNF- α during the first one, three, and six hours after a singular skin burn injury, singular smoke inhalation injury, and a combination involving both the traumas. The data were compared with the data from control rats that only received preparation and mechanical ventilation. The TNF- α serum levels and intraalveolar IL-6 concentrations were also measured. One hour after trauma, there was a significant difference in the TNF- α concentration between the controls and both the singular traumas (control vs burn P < .0444 and control vs smoke P < .005) and between the inhalation injury and the combined trauma (smoke vs burn + smoke P < .0084). After three and six hours, no significant differences among the groups were observed. Compared with the controls, both the singular skin burn and smoke inhalation injuries led to increased intraalveolar TNF- α excretion, whereas the combined trauma showed the least intraalveolar TNF- α levels at three and six hours post-trauma. These findings differed from the serum TNF- α levels. Compared with the IL-6 levels, we observed a negative correlation within the intraalveolar cytokine concentrations after one hour ( r = −.809), three hours ( r = −.627), and six hours ( r = −.746). This study confirms the importance of the intraalveolar cytokine reaction in the early posttraumatic stage after a combined burn and inhalation injury. The differences between the combined and singular traumas indicate that TNF- α plays a role in the immunologic hyporesponsiveness of the lung and therefore in the systemic pathophysiological pathway, that often leads to patient mortality. In addition, an inverse correlation between TNF- α and IL-6, both classical markers of inflammation, in the intraalveolar space was observed.